Extracellular vesicles—a new player in the development of urinary bladder cancer - Damian Kasiński; Kamil Szeliski; Tomasz Drewa; Marta Pokrywczyńska (Therapeutic Advances in Medical Oncology)
Bladder cancer was the 10th most commonly diagnosed cancer worldwide in 2020. Extracellular vesicles (EVs) are nano-sized membranous structures secreted by all types of cells into the extracellular space. EVs can transport proteins, lipids, or nucleic acids to specific target cells. What brings more attention and potential implications is the fact that cancer cells secrete more EVs than non-malignant cells. EVs are widely studied for their role in cancer development. This publication summarizes the impact of EVs secreted by urinary bladder cancer cells on urinary bladder cancer development and metastasis. EVs isolated from urinary bladder cancer cells affect other lower-grade cancer cells or normal cells by inducing different metabolic pathways (transforming growth factor β/Smads pathway; phosphoinositide 3-kinase/Akt pathway) that promote epithelial–mesenchymal transition. The cargo carried by EVs can also induce angiogenesis, another critical element in the development of bladder cancer, and modulate the immune system response in a tumor-beneficial manner. In summary, the transfer of substances produced by tumor cells via EVs to the environment influences many stages of tumor progression. An in-depth understanding of the role EVs play in the development of urinary bladder cancer is crucial for the development of future anticancer therapies.